Synopsis: Institutions and public agricultural investments: A qualitative study of state and local government spending in Nigeria - Mogues, Tewodaj; Olofinbiyi, Tolulope (International Food Policy Research Institute, 2016)
There is a renewed attention to the performance of the ag-ricultural sector in Nigeria given its potential to serve as an engine of pro-poor growth, create jobs, and support economic diversification. Strategies to further transform agriculture need to be accompanied by efficient and effective public expenditures. In addition to analysis of the size and quality of agricultural spending, an understanding of the political-institutional setting within which public spending decisions are made is important. However, there is little known about the policy and political processes through which public agricultural expenditure al-locations are decided upon. This policy note synthesizes the findings of an empirical analysis of how the political and budget institutions of the states and Local Government Areas (LGA) of Nigeria affect the incentives of actors involved in the public agricultural finance process, shape the interactions between them, and ultimately influence expenditure allocations.